Penentuan Nilai Penyerapan Suara Pada Panel Dinding Beton Busa Sebagai Panel Alternatif Yang Ramah Lingkungan - Zulfian, Zulfian; Abdullah, Abdullah; Fahridhal, Fahridhal (Jurnal Rekayasa Kimia & Lingkungan, 2011)
Panel of foam concrete wall is a type of membrane panel which has maximum sound absorption and can create quite and environmentally friendly room. The purpose of this study was to determine the magnitudeof the sound absorption value using the Sabine formula in Reverberation Chamber at Syiah Kuala University acoustic laboratory. The result of this study show that peak value curve sound absorption of 0.67 accurs at the frequency of 250 Hz, and painting of the panel surface can increase the value of sound absorption to be 0.76 at the frequency of 250 Hz,but the slope of sound absorption value sharply decreased to be 0.07at the frequency of 1000 Hz. Treatment on the panel surface can increase or decrease the value of sound absorption especially at the low frequency regions.Keywords: Panel of foam concrete wall, Sabine formula, The value of sound absorption